Youth Political Participation in Village Development in Indramayu District (Study at Pabean Udik Village): Partisipasi Politik Anak Muda Dalam Pembangunan Desa di Kabupaten Indramayu (Studi Pada Desa Pabean Udik) (Journal of Political Issues, 2023)
This research is motivated by the increasingly incessant village development driven by village funds. The problem that arose later was that the abuse of village funds had an impact on results that did not meet the needs of the residents. On the other hand, village development requires the citizen participation to improve the quality of life and welfare of village communities. In this context, youth as one element of the community tends to be less involved in village development activities. This research aims to reveal village development from the perspective of young people and their political participation in village development by taking a study in Pabean Udik Village, Indramayu District, Indramayu Regency. This research uses a quantitative descriptive approach. Data collection was carried out by interviewing using a questionnaire. The findings in this study indicate that according to young people, development in Pabean Udik Village must prioritize village infrastructure development and is considered to have had a positive impact. On the other hand, the level of youth political participation in development in Pabean Udik Village is quite low. Participation is also limited to voting activities. The cause is a structural obstacle in the form of the government's role that has not been optimal in providing information services and pro-active citizen involvement. Information media is still conventional through bulletin boards and banners. Not yet adjusting to the development of digital media which is more accessible to citizens, especially young people.
Keywords: Political Participation; Youth; Village Development